Electrical Conductance Analysis of Solanum Lycopersicum under Biotic Stress - TEUMA MBEZI, Michel; Najeh, Sameh; Zachée, Ambang; Fouda H, Ekobena; Timoleon C, Kofané (Transactions on Engineering and Computing Sciences, 2020)
Our purpose is to provide different parameters of control from which one can identify a sick plant before the appearance of the first symptoms. We made a stochastic analysis and an analysis according to the theory of information, to deduce those characteristics parameters. It came out from our analysis that the DSP of health plant is above the DSP of the sick plant. Generally, the DSP of health and treated plant is above the DSP of sick and treated plant. However there is an overlapping between the DSP of sick and treated plant, and the health one for the whole value of the normalized reduced frequency. The average conductance of health plant is higher than the average conductance of sick plant. We also observed that, average conductance of health and treated plant is lower than the average conductance of sick and treated plant. The standard deviation of health plant is higher than the standard deviation of sick plant. We also observed that, standard deviation of health and treated plant is lower than the standard deviation of sick and treated plant. The electric conductance signal G(ω,t) of Solanum lycopersicum leaf plant is not a statistics process in the broad sense (SSL). Electric conductance G(ω,t) of the plant is a non ergotic signal. The entropy of the sick plant is higher than the entropy of the health one. Those parameters can be used during the development of informatics application, and can be used in I.O.T. (internet of thing)